COMPLEXES OF 2-HYDROXY- 4-DIMETHOXYPHENYL-6-BENZYLOXY PHENYLPYRIMIDINE WITH SOME METAL IONS - Najeeb, Dina A (Al-Nahrain Journal of Science, 2018)
New complexes of the ligand 2-hydroxy-4-dimethoxyphenyl-6-benzyloxy phenylpyrimidinewith metal ions Cr (III), Fe (III), Co (II), Ni (II) and Cu (II) were prepared in alcoholic medium.The prepared complexes where characterized by magnetic susceptibility, molar conductance,FTIR, Uv-Vis. The data showed that these complexes have the composition of [ML2].